(untitled) (Majalah Kedokteran Bandung, 2024)
Various phacoemulsification techniques are commonly used, with phaco-chop and stop-and-chop techniques as the most popular ones. Phacoemulsification inevitably leads to endothelial cell destruction, which, in severe cases, might result in vision impairment. This study aimed to compare endothelial cell characteristics between two phacoemulsification procedures, phaco-chop, and stop-and-chop, in patients with soft to moderate nucleus cataracts. This study was conducted on 142 patients at the National Eye Center of Cicendo Hospital between April and August 2018. Of those, 66 patients underwent the phaco-chop technique, while 76 patients underwent the stop-and-chop technique. Intraoperative parameters such as effective phaco time (EPT), phaco time, average power, and duration were recorded. Endothelial density, hexagonality, coefficient of variation (CV), and central cornea thickness (CCT) were also recorded before surgery, as well as one week and four weeks after surgery. Mean power, EPT, phaco time, and duration in the phaco-chop group were significantly lower than in the stop-and-chop group. Mean (SD) endothelial density at one-week and four-week evaluation in the phaco-chop group were considerably lower than in the stop-and-chop group (p-value=0.024 and p-value=0.000, respectively). Mean (SD) CV at one-week evaluation in the phaco-chop group was significantly higher compared to a stop-and-chop group, 43.3 (8.0) versus 40.0 (6.7) % (p-value=0.009). Mean (SD) hexagonality at four-week evaluation in the phaco-chop group was significantly higher compared to a stop-and-chop group (43.1 (17.6) versus 48.7 (13.2) respectively, p-value=0.045). Phaco-chop technique have significantly lower EPT, average power, phaco time, and surgery duration than stop-and-chop techniques at one-week and four-week evaluation after phacoemulsification.